2013
DOI: 10.3126/ajms.v5i2.5483
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effects of Carvedilol and Curcuma longa against Cisplatin-Induced Nephrotoxicity in Rats

Abstract: Objective: Goal of this study is to investigate the effects of carvedilol (5 mg/kg, p.o), aqueous and methanolic extract of Curcuma longa (500mg/kg, p.o) against cisplatin induced renal damage in Wistar rats after a single intraperitoneal injection of 7.5mg -1 . Methods: Wistar rats were randomly divided into 7 groups (n=10). Rats in group I were normal control received normal saline (5 ml/kg; i. p.) on day zero, while group VIa and VIb were vehicle control, received carboxymethyl cellulose (2.5 ml/kg; p.o.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In this study, carvedilol administered in the presence of doxorubicin and 5‐FU significantly decreased creatinine level compared with administration of the toxicants alone. This is a pointer to the nephroprotective effect of carvedilol, an observation supported by the findings of Wong et al and Pathak et al . Coadministration of carvedilol and diltiazem in the presence of the 2 toxicants resulted in a significant decrease in creatinine level compared with administration of the toxicants alone.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, carvedilol administered in the presence of doxorubicin and 5‐FU significantly decreased creatinine level compared with administration of the toxicants alone. This is a pointer to the nephroprotective effect of carvedilol, an observation supported by the findings of Wong et al and Pathak et al . Coadministration of carvedilol and diltiazem in the presence of the 2 toxicants resulted in a significant decrease in creatinine level compared with administration of the toxicants alone.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, the plant exhibits protective effects in animal models of myocardial (Tanwar, Sachdeva, Golechha, Kumari, & Arya, ; Yang, Wu, Li, & You, ), pulmonary (K. Liu et al, ; Sakurai et al, ), and renal injury (Mohamad et al, ; Sharma, Kulkarni, & Chopra, ). In rats, C. longa attenuated nephrotoxicity of gentamicin and cisplatin (Elgazar & AboRaya, ; Pathak, Rajurkar, Tarekh, & Badgire, ) and also protected the heart, liver, and kidneys from DOX‐induced toxicity (Mohamad et al, ). Curcumin also protected the kidneys against cadmium‐induced nephrotoxicity (K. S. Kim et al, ), ischemia–reperfusion injury (F. Liu et al, ), and, in the form of nanoparticles, against rhabdomyolysis‐induced kidney injury (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Varuna (Crataeva nurvala): Some research works shows that Crataeva nurvala's alcoholic extract given in doses of 250 and 500 mg/kg for 10 days, it demonstrated protective effect against cisplatin's 5 mg/kg-induced nephrotoxicity. The findings indicated that the alcoholic extract considerably changed the dysfunction of renal proximal tubule cells by lowering blood urea nitrogen, creatinine, lipid peroxidation, glutathione, and catalase concentrations [33].…”
Section: Shunthi (Zingiber Officinale): Whenmentioning
confidence: 93%